Social interactive television immersive shared experiences and perspectives - Cesar, Pablo; Geerts, David; Chorianopoulos, Konstantinos 1975- (Premier reference source, 2009)
"This book discusses the advent of social interactive television with its complex opportunities and challenges for media researchers and others today" - Provided by publisher